An experimental method for evaluation of the snow albedo effect on near‐surface air temperature measurements. (3rd December 2018) - Musacchio, Chiara; Coppa, Graziano; Merlone, Andrea
Abstract : Among the many effects influencing the accuracy in near‐surface air temperature measurements ( t air ), solar radiation plays a key role. While numerous technical solutions have been developed to protect temperature sensors from direct solar radiation, few studies are available to evaluate the warming due to reflected radiation. Changes in surface albedo influence the measurement results of t air and, in the case of sensors positioned above a snow‐covered surface, this effect is amplified due to the larger amount of radiation reflected. As a task of the European project MeteoMet, a design for a metrological experimental setup and associated measurement method was studied, to quantify errors in temperature records when thermometers in solar shields and compact automatic weather stations are positioned above snow‐covered soil. An operative model was developed to minimize quantities of influence and uncertainties, while the experimental protocol proposed guidance on instruments required, sensor characterization, field experiment installations and site characteristics. The procedure described can be implemented by users without specific metrological skills: staff of hydro‐meteorological agencies with commonly used equipment and technicians of manufacturing companies can easily perform the measurements, characterize the instruments and evaluate the total maximum effect in terms of temperature increase and a correction factor or curve for specific typologies of instruments. The work presented is part of wider activities aimed at completing the calculation of an uncertainty budget on near‐surface air temperature measurement. Abstract : Snow‐covered surfaces significantly reflect solar radiation, affecting the accuracy of near‐surface air temperature measurements. Solar shields of different kinds and shapes are not optimized to protect the sensors from backward overheating and differences of more than 1 °C can be observed in the case of the presence of snow below the measuring instruments. A theoretical and experimental model is presented for evaluating the several parameters that maximize the amplitude of this effect and for its inclusion in the temperature measurement uncertainty budget.